ANTESENDEN KEPUTUSAN PEMBELIAN TANAMAN HIAS PADA MASA PANDEMI DI SURAKARTA - Damayanti, Rizki Putri; Susanti, Ari (JURNAL LENTERA BISNIS, 2021)
The study was conducted to find out that the decision to purchase ornamental plants during the Covid-19 pandemic was influenced by several factors such as Trend, Lifestyle, Price, and Uniqueness. The variables used in this study are Trend (X1), Lifestyle (X2), Price (X3), Uniqueness (X4) and Purchase Decision (Y). This research was conducted with a quantitative approach, one of which is purposive sampling using the roscoe count so that 100 respondents can be taken who are ornamental plant hobbyists or ornamental plant consumers during the pandemic. The collection technique uses a Likert scale to make it easier for respondents to fill out the questionnaire. Data analysis in this research is multiple linear regression analysis. This study uses the SPSS 21 tool to see the results of the data obtained. The results of this study Trend, Lifestyle and Uniqueness have a positive and significant influence on purchasing decisions of ornamental plants during the pandemic. Then the price does not have a positive and significant influence on purchasing decisions during the pandemic.Keywords: Trend, Lifestyle, Price, Uniqueness, Purchase Decision